2020
DOI: 10.5713/ajas.19.0199
|View full text |Cite
|
Sign up to set email alerts
|

Physiological impact on layer chickens fed corn distiller’s dried grains with solubles naturally contaminated with deoxynivalenol

Abstract: Objective: An experiment was conducted to investigate the response of laying hens fed corn distiller' s dried grains with solubles (DDGS) that are naturally contaminated with deoxynivalenol (DON). Methods: One hundred and sixty 52-week-old Lohmann Brown Lite hens were randomly allotted to five dietary treatments with 8 replicates per treatment. The dietary treatments were formulated to provide a range of corn DDGS contaminated with DON from 0% to 20% (i.e., 5% scale of increment). All laying hens were subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
5
5
0
Order By: Relevance
“…The present study demonstrated that TOXO HP and XL binders could effectively counteract AFB 1 , DON, and OTA-induced adverse effects on laying hens. In agreement with previous studies [ 21 , 22 , 23 ], chicks exposed to AFB 1 , DON, and OTA, alone or in combination, reduced feed intake, total egg weight, and egg-laying rate, while they increased feed/egg ratio and mortality during various experimental periods. Meanwhile, mycotoxins also decreased the eggshell strength and increased DON residue in eggs relative to the control group, which was in agreement with previous reports [ 21 , 24 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study demonstrated that TOXO HP and XL binders could effectively counteract AFB 1 , DON, and OTA-induced adverse effects on laying hens. In agreement with previous studies [ 21 , 22 , 23 ], chicks exposed to AFB 1 , DON, and OTA, alone or in combination, reduced feed intake, total egg weight, and egg-laying rate, while they increased feed/egg ratio and mortality during various experimental periods. Meanwhile, mycotoxins also decreased the eggshell strength and increased DON residue in eggs relative to the control group, which was in agreement with previous reports [ 21 , 24 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, the histopathological results showed that mycotoxins induced severe damage in small intestine of laying hens, as evidenced by villous atrophy and fracture, degeneration, necrosis, and desquamation of the villous epithelial cells, hemorrhage and inflammatory cell infiltration in submucosa and lamina propria, and (or) goblet cell hyperplasia in the intestinal gland, along with reduced villus height, villus height/crypt depth and crypt depth in the duodenum, jejunum, and (or) ileum. These findings were similar to previous studies that animals consumed diets contaminated with AFB 1 , DON, and OTA, alone or in combination, could induce intestine injury, thus reducing nutrient utilization efficiency and causing poor performance [ 23 , 39 , 40 , 41 ]. Interestingly, dietary supplementation with TOXO HP and XL binders alleviated mycotoxins-induced negative effects on histopathological alteration in small intestine of laying hens.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…(2014) investigated the effect of feeding diets containing DON-contaminated DDGS (16 mg/kg DON) to pigs and reported that inclusion of 25% DON-contaminated DDGS in diets decreased BW gain ( BWG ) and feed intake ( FI ). However, Wickramasuriya et al. (2020) reported that increasing inclusion levels of DON-contaminated DDGS (5 mg/kg DON) from 0 to 20% in diets did not affect productive performance and egg quality of laying hens.…”
Section: Introductionmentioning
confidence: 97%
“…As a matter of fact, the use of antibiotics as a feed additive (antibiotic growth promoter, AGP) has been banned in several countries and is thus decreasing globally. In addition to diseases, various stress factors, such as drastic thermal changes [ 2 ], deteriorated environments [ 3 ], and nutritional imbalance [ 4 ], which also adversely affect domestic animal productivity, are increasingly attracting considerable attention from animal scientists, field managers of animal farms, and operation staff in the livestock industry.…”
Section: Introductionmentioning
confidence: 99%